Pemetaan Indeks Pembangunan Manusia Menggunakan Algoritma K-MEANS - Ufil Hidayatul Laili; Firman Santoso; Sunardi (Fakultas Sains dan Teknologi, Universitas Ibrahimy, 2026)
The Human Development Index (HDI) was introduced by the United Nations Development Programme (UNDP) as an important indicator for measuring the success of efforts to improve the quality of human life. Development initiatives implemented by the government represent efforts to promote public welfare and prosperity, including development in infrastructure, education, health, and economic sectors. The primary target of these development programs is the community, with the expectation that such initiatives will address various societal issues, including poverty, unemployment, school dropout rates, health problems, and social inequality. Development programs carried out by both central and regional governments are closely associated with the level of HDI achievement. One example is East Java Province, particularly Situbondo Regency, where the HDI has consistently increased from year to year. In 2019, the HDI of Situbondo Regency was 67.09, increasing to 67.38 in 2020, 67.78 in 2021, and 68.25 in 2022. This study aims to classify regencies/cities in East Java Province based on HDI indicators from 2019 to 2022. In addition to supporting future program planning, the classification conducted from 2019 to 2022 also serves as an evaluation of the development targets implemented by the East Java Provincial Government during that period, particularly in relation to programs for improving human quality of life.